Physical and Mechanical Properties of High-Strength Heavy Concrete Using Recyclable Asphalt Waste - Isroilova Durdona; Ergashev Doston; Maxammatov Muzaffar, (European Journal of Life Safety and Stability (2660-9630), 2022)
In this research the authors research of the physical and mechanical properties of high-strength heavy concrete and improve the quality of concrete constructions. High-strength heavy concrete that have a water/binder ratio between 0.500 and 0.60 are usually more durable than ordinary concrete not only because their capillarity and pore networks. So, the concrete sample specimens were tested for physical and mechanical properties which are related to durability.